Implementasi Pemungutan Suara Ulang Dalam Undang-Undang Nomor 7 Tahun 2017 - Leni Karlina; Mila Sari; Putri Yanti; Dewi Hariyanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The validity of voting results depends on various factors, one of which is the completeness and validity of the ballot paper, which is one of the important elements in elections that voters use to mark their choices. Based on the circular letter of the Tanjungpinang City General Election Supervisory Agency (Bawaslu) Number: 136/PM.00.02/K.KR-06/02/2024 there were 2 TPS taking place at TPS 006 and TPS 015 there were 115 x 5 ballot papers that were not signed by KPPS so that the ballot box is open during voting, raising questions regarding its validity and the potential for fraud in the voting process. This research aims to analyze the consequences of not signing the ballot paper and its impact on the validity of the voting results, as well as the conditions for re-voting. The research method that researchers use is normative juridical, namely based on basic legal materials. This research was conducted by examining theories, concepts, legal principles and laws and regulations that are relevant to this research topic. The research results show that there are several factors that cause ballot papers not to be signed, including KPPS negligence, lack of socialization, and misinterpretation of regulations. Thus, re-voting is a step that can be taken to ensure the validity and legitimacy of voting results by considering various factors, including the number of unsigned ballot papers, the potential for fraud, and the impact on democratic stability.